Development of the EDU-ECON E-Module Based on Problem-Based Learning to Enhance Students’ Critical Thinking Skills on the Topic of Economic Actors - Yuliana, Nadhia; Dewi, Retno Mustika (Jurnal Paedagogy, 2025)
This development research aimed to create a problem-based learning (PBL)-based EDU-ECON e-module and to evaluate its feasibility, effectiveness, and practicality using the ADDIE development model. The research subjects were 36 students from Class X-3 at State Senior High School 21 Surabaya. The research instruments included interview guidelines for the economics teacher, questionnaires, and pre-test and post-test assessments. Data were analyzed using descriptive statistics and t-tests. The results showed that the developed e-module was feasible for use, with average validation scores of 92% from media experts and 90.67% from content experts, classifying it as highly valid. The module’s effectiveness was also high, with an N-gain value of 0.76, indicating its ability to improve students’ critical thinking skills. Furthermore, student responses were positive, with a practicality score of 82.45%, categorized as very practical. Therefore, the developed e-module is both feasible and effective in enhancing students’ critical thinking skills.